SOSIALISASI TANGGAP BENCANA BANJIR PADA MASYARAKAT LANSIA DI DESA LOK CANTUNG, KABUPATEN BANJAR, KALIMANTAN SELATAN - Ashar Alamsyah; Pathurrahman; Bacharuddin Ali Akhmad; Akhmad Reza Haitami; Chris Muhammad Akbar Hafizan; Febriaulfah Yanra Katimenta; Julia Fitriani; Latifah Azlina; Lidya Nur Aini Putri; Royana (Wadah Inovasi Indonesia, 2022)
Flooding is a natural phenomenon caused by man because of some of the factors; rain, river conditions, upstream conditions, raising areas, and tides. The purpose of this study was to describe the role of the community and village officials as well as community service students in the Flood Disaster Response Socialization program for the Elderly Communities in Lok Cantung Village with qualitative research method. The results showed that the progress of the response of the elderly and the community in Lok Cantung village could be concluded that it was going well. Direct evidence can be seen from the facilities and infrastructure owned by Lok Cantung Village which are very good and adequate. In the aspect of reliability, village officials are reliable in mastering their respective duties and functions, as well as existing tools to provide comfort for the community. Then in the aspect of responsiveness, village officials have been good in providing services. However, the lack of community participation.